2015
DOI: 10.1371/journal.pone.0124199
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Resistance of Helicobacter pylori in Taiwan after the National Policy to Restrict Antibiotic Consumption and Its Relation to Virulence Factors—A Nationwide Study

Abstract: ObjectiveThe Taiwan Government issued a policy to restrict antimicrobial usage since 2001. We aimed to assess the changes in the antibiotic consumption and the primary resistance of H. pylori after this policy and the impact of virulence factors on resistance.MethodsThe defined daily dose (DDD) of antibiotics was analyzed using the Taiwan National Health Insurance (NHI) research database. H. pylori strains isolated from treatment naïve (N=1395) and failure from prior eradication therapies (N=360) from 9 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 29 publications
4
61
0
1
Order By: Relevance
“…[54][55][56] When examining the prevalence of CagA-positive HP infection, the rate is ;60% in Western countries while similar studies in Eastern Asian populations suggest that it is nearly 90%. [57][58][59][60][61] Another interesting observation reported in our previous 28 and current studies is that CagA expression is more frequent in HP-dependent cases than in HP-independent cases, and that time to response to HPE is shorter in cases that express CagA. These findings are in line with the fact that Asian gastric MALT lymphoma patients have a higher response rate to HPE than Western patients (84.1% vs 73.8%; P 5 .0001).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[54][55][56] When examining the prevalence of CagA-positive HP infection, the rate is ;60% in Western countries while similar studies in Eastern Asian populations suggest that it is nearly 90%. [57][58][59][60][61] Another interesting observation reported in our previous 28 and current studies is that CagA expression is more frequent in HP-dependent cases than in HP-independent cases, and that time to response to HPE is shorter in cases that express CagA. These findings are in line with the fact that Asian gastric MALT lymphoma patients have a higher response rate to HPE than Western patients (84.1% vs 73.8%; P 5 .0001).…”
Section: Discussionsupporting
confidence: 85%
“…63 Peng et al also reported that the frequency of CagA-positive strains of HP was significantly higher (P , .05) in patients with gastric DLBCL (MALT) than in those with gastric MALT lymphomas or gastritis. 64 Using polymerase chain reaction analysis (supplemental Methods), 60,61 we found that all 11 HP strains isolated from patients with HP-dependent gastric lymphomas (5 gastric DLBCLs and 6 gastric MALT lymphomas) are cagA gene positive (data not sown). In addition to the distinct prevalence of CagA-positive HP infection in Asian populations, East Asian CagA carries a EPIYA-D segment, which differs from the EPIYA-C motif commonly seen in Western CagA variants.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in resistance profile over time may be caused by increased clarithromycin usage for pneumonia and decreased metronidazole usage for diarrhea because of a gradual increase in hygienic conditions nationwide [30]. Therefore, the prevention of unnecessary macrolide consumption may decrease the development of clarithromycin resistance [52,53]. In Japan, clarithromycin consumption increased fourfold between 1993 and 2000, which resulted in a fourfold increase in clarithromycin resistance [51].…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy to improve the efficacy of currently used regimens could be the implementation of a national program to restrict antibiotic consumption, especially macrolides and nitroimidazoles. In Taiwan, this policy has probably contributed to a low primary clarithromycin and metronidazole resistance of H. pylori (23).…”
Section: Discussionmentioning
confidence: 99%